Efficacy of Dunaliella salina (Volvocales, Chlorophyta) in Salt Refinery Effluent Treatment - Raja, R.; Anbazhagan, C.; Ganesan, V.; Rengasamy, R. (Asian Journal of Chemistry, 2016)
The halotolerant green alga, Dunaliella salina (Dunal) Teod. isolated from the salt evaporation ponds (Kelambakkam near Chennai) was evaluated for its potential in the treatment of salt refinery effluent. The alga was grown in 100% effluent and its mixtures, viz., effluent + seawater and effluent + basal medium in the ratio of 1 : 1. Experiments were conducted for a period of 18 d. At every six days interval, concentrations of the pigments Chl-a, Chl-b and β-carotene of the organism were recorded. UV absorption spectrum was taken to confirm the presence of β-carotene isomers at 443 nm and 475 nm. Initial and final physico-chemical features of the effluent and its mixtures namely appearance, odour, TDS, turbidity, pH, hardness, BOD, COD, NO4—N, NO2—N, NH4—N, PO4—P, K, Ca, Mg, Na, SO4, Fe, CI, F, Tidy's test and SiO2 were recorded. The amount of heavy metals Ba, Al, Ag and St present in 100% effluent were also recorded. The amount of β-carotene was found high when the alga was grown in 100% effluent compared to its mixtures. Among the three different experiments, the alga grown in 100% effluent was able to reduce a maximum 77.5% of K followed by 72.5% of Na. The levels of BOD and COD were also reduced up to 54.5% and 50.5%, respectively. The removal percentages of heavy metals, viz., Ba, Al, Ag and St by the alga at the above condition were 56.5, 46.0, 32.4 and 4.8%, respectively.